2014
DOI: 10.1016/j.jgr.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A review on the medicinal potentials of ginseng and ginsenosides on cardiovascular diseases

Abstract: Ginseng is widely used for its promising healing and restorative properties as well as for its possible tonic effect in traditional medicine. Nowadays, many studies focus on purified individual ginsenoside, an important constituent in ginseng, and study its specific mechanism of action instead of whole-plant extracts on cardiovascular diseases (CVDs). Of the various ginsenosides, purified ginsenosides such as Rb1, Rg1, Rg3, Rh1, Re, and Rd are the most frequently studied. Although there are many reports on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
241
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(249 citation statements)
references
References 80 publications
2
241
0
6
Order By: Relevance
“…1A) is the pivotal bioactive ingredient responsible for its beneficial pharmaceutical effects. Recently, accumulating evidence has demonstrated that Rg1 exhibits significant cardioprotective activities against I/R injury through numerous mechanisms, primarily attributed to the inhibition of cell apoptosis and resistance to oxidative stress [23]. …”
Section: Introductionmentioning
confidence: 99%
“…1A) is the pivotal bioactive ingredient responsible for its beneficial pharmaceutical effects. Recently, accumulating evidence has demonstrated that Rg1 exhibits significant cardioprotective activities against I/R injury through numerous mechanisms, primarily attributed to the inhibition of cell apoptosis and resistance to oxidative stress [23]. …”
Section: Introductionmentioning
confidence: 99%
“…A-44 (Kobashi, 2004). Ginsenosides produced a variety of pharmacological activities such as antiinflammatory, anti-oxidant, anti-cancer and vasorelaxation (Lee and Kim, 2014;Leung and Wong, 2010).…”
Section: Ginsenosidesmentioning
confidence: 99%
“…Hyperforin, a triterpenoid, demonstrated to be an effective free radical scavenger, more potent than Trolox and N-acetylcysteine [43] . Ginsenoside Rg2, a triterpenoid commonly found in ginseng, has also been reported to have antioxidant properties by reducing the oxidationinduced damage of erythrocyte membrane [44] . The triterpenoid platycodigenin also showed potent antioxidant capacity against peroxynitrite, with a 2.35-fold increase in total oxidant-scavenging capacity value compared with glutathione [45] .…”
Section: Table 1: Antioxidant Activities and Total Phenolic Flavonoimentioning
confidence: 99%